In vivo near-infrared imaging of fibrin deposition in thromboembolic stroke in mice. - Yi Zhang (Public Library of Science (PLoS), 2012)
Objectives Thrombus and secondary thrombosis plays a key role in stroke. Recent molecular imaging provides in vivo imaging of activated factor XIII (FXIIIa), an important mediator of thrombosis or fibrinolytic resistance. The present study was to investigate the fibrin deposition in a thromboembolic stroke mice model by FXIIIa-targeted near-infrared fluorescence (NIRF) imaging. Materials and methods The experimental protocol was approved by our institutional animal use committee. Seventy-six C57B/6J mice were subjected to thromboembolic middle cerebral artery occlusion or sham operation. Mice were either intravenously injected with the FXIIIa-targeted probe or control probe. In vivo and ex vivo NIRF imaging were performed thereafter. Probe distribution was assessed with fluorescence microscopy by spectral imaging and quantification system. MR scans were performed to measure lesion volumes in vivo, which were correlated with histology after animal euthanasia. Results In vivo significant higher fluorescence intensity over the ischemia-affected hemisphere, compared to the contralateral side, was detected in mice that received FXIIIa-targeted probe, but not in the controlled mice. Significantly NIRF signals showed time-dependent processes from 8 to 96 hours after injection of FXIIIa-targeted probes. Ex vivo NIRF image showed an intense fluorescence within the ischemic territory only in mice injected with FXIIIa-targeted probe. The fluorescence microscopy demonstrated distribution of FXIIIa-targeted probe in the ischemic region and nearby micro-vessels, and FXIIIa-targeted probe signals showed good overlap with immune-fluorescent fibrin staining images. There was a significant correlation between total targeted signal from in vivo or ex vivo NIRF images and lesion volume. Conclusion Non-invasive detection of fibrin deposition in ischemic mouse brain using NIRF imaging is feasible and this technique may provide an in vivo experimental tool in studying the role of fibrin in stroke.